Comparison of two different doses of bleomycin in electrochemotherapy protocols for feline cutaneous squamous cell carcinoma nonsegregated from ultraviolet light exposure - Dos Anjos, Denner S. [UNESP]; Sierra, Oscar R. [UNESP]; Spugnini, Enrico P.; De Nardi, Andrigo B. [UNESP]; Fonseca-Alves, Carlos E. [UNESP] (Springer Nature, 2020)
Cutaneous squamous cell carcinoma (cSCC) is one of the most common skin tumors in cats due to chronic exposure to ultraviolet light. Local treatments such as electrochemotherapy (ECT) promote disease control or even complete remission. We hypothesize that cats could benefit from treatments using bleomycin at reduced dosages. A prospective nonrandomized single-blind study evaluated the clinical parameters, site lesion, staging, disease-free interval (DFI) and survival time by comparing the standard dose of bleomycin(15,000 UI/m2) (n = 22) with a reduced dose (10,000 UI/m2) (n = 34) in cats with cSCC that underwent ECT as the sole treatment modality. No statistically significant difference in DFI or overall survival was observed between the 2 groups. A higher DFI was found in cats with a small tumor size (less than 0.33 cm3) compared with that for cats with a large tumor size (P = 0.045). Furthermore, a reduced overall survival time for cats with a higher stage in the standard group SG (T3 and T4) (P = 0.004) was observed when compared to that for cats with a lower stage (T1 and T2). In conclusion, ECT using both doses of bleomycin may achieve the same response rate in terms of the overall response, DFI, and overall survival.